Production Model to increase OEE through the application of Lean Manufacturing and Total Production Maintenance tools in animal feed manufacturing SMEs - Espinoza Monge, Angelo Paolo de Jesus (2022)
This research proposes a production model capable of increasing the Overall Equipment Effectiveness (OEE) using the methodology Lean Manufacturing and TPM. The case study is a company in the livestock industry where the 4 phases of the model were implemented. The first phase is the implementation of the Poka-Yoke tool. Then follows the implementation of the MRP. After that, the implementation of a preventive maintenance plan and the last phase is implementing the 5’s tool. After validation in the Arena software and the simulation of the implemented production model, it is shown that the OEE indicator increases by 15.69%, managing to achieve a productivity improvement.